Diversity in urban health collaborations in Latin America : a temporal multilayer network analysis of the SALURBAL project (2021)
The need to take advantage of diversity benefits in developing projects has increased to achieve their purposes. We analyze the diversity of a transformative and groundbreaking project like SALURBAL by characterized the project's evolving network considering the activities that constitute the research process through a temporal multilayer network approach. This study could be a framework to evaluate the diversity project?s growth and sustainability by two measures: (1) we proposed a measure of the diversity within the project's activities, considering the inter and intra collaborations of the participants and their attributes (discipline, domain, sector, seniority, gender, country, and city); (2) we assessed how different the diverse collaborations between the project's activities were. We discovered that (1) the SALURBAL project has understood balance diversity to achieve better performance by giving each activity strength in some attributes' diversity...